PENGARUH KEADILAN PAJAK, SISTEM PERPAJAKAN, DISKRIMINASI PAJAK DAN ETIKA UANG (MONEY ETHIC) TERHADAP NIAT WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK (Studi Empiris Pada Wajib Pajak Orang Pribadi Terdaftar di KPP Pratama Semarang Candisari) - Salma Azzahra Kurnia; Faisal Faisal (Diponegoro Journal of Accounting, 2022)
This study aimed to analyze factors affect taxpayer’s intention about the tax evasion. These factors are the fairness, tax system, discrimination and money ethic against the taxpayer’s Intention about the tax evasion. The population in this study are individual taxpayers who registered in KPP Pratama Semarang Candisari. In this research used primer data include questionnaires, which are distributed via google forms to personal obligation tax. The sample technique in this study is determined by sampling convenience method. The data were analysed by SmartPLS 3.0.      The results of this study show that the fairness, tax systems, discrimination and money ethic have a positive and significant effect on taxpayer’s intention about the tax evasion. These findings suggest that tax evasion is viewed as unethical acts. Direktorat Jenderal Pajak needs to hold socialization that tax revenue are importance for the development in order to increase awareness of taxation, especially in Semarang.